Culture Shock Childfree Phenomenon in Indonesia from A Biopsychological and Humanistic Perspective - Supriyani, Ani; Fitriana, Nina (International Journal Labs, 2025)
The childfree phenomenon—voluntarily choosing not to have children—has emerged as a controversial lifestyle choice in Indonesia, generating significant discourse around reproductive autonomy, cultural values, and mental well-being. This study examines the Culture Shock Childfree Phenomenon in Indonesia from A Biopsychological and Humanistic Perspective, analyzing it through integrated biopsychological and Maslow’s humanistic theoretical frameworks. Employing a library research methodology, this study systematically reviews and synthesizes scholarly literature, including peer-reviewed journal articles, books, and empirical studies from multiple databases, to construct a comprehensive theoretical analysis. The biopsychological perspective reveals that childfree decisions are influenced by complex interactions between reproductive health conditions, neurobiological factors, environmental contexts, and psychological characteristics across physiological, ontogenetic, evolutionary, and functional dimensions. Maslow’s humanistic framework demonstrates that contemporary redefinitions of human needs position childfree choices as expressions of self-actualization and personal autonomy rather than deficiencies. However, Indonesia’s collectivist cultural orientation generates substantial social stigma and psychological pressure against childfree individuals, resulting in culture shock experiences characterized by value conflicts, social isolation, and identity negotiation. The findings suggest that childfree individuals in Indonesia navigate tensions between personal autonomy and cultural expectations, requiring mental health support systems and broader societal awareness to reduce stigmatization. This research contributes theoretically by integrating biological and humanistic perspectives on reproductive choice, and practically by informing counseling approaches and social policies that respect reproductive diversity while acknowledging cultural contexts.